Answer: [tex] {( \frac{2}{5}) }^{ – 4} \\ [/tex] Step-by-step explanation: [tex]( \frac{2}{5} ) ^{ – 2} \times {( \frac{2}{5} )}^{ – 2} \\ = {( \frac{2}{5} )}^{ – 2 + ( – 2)} \\ = {( \frac{2}{5} )}^{ – 2 – 2} \\ = {( \frac{2}{5} )}^{ – 4} [/tex] it done by the formula :– [tex] {x}^{m} \times {x}^{n} = {x}^{m + n} [/tex] Where bases are same and we have to multiply them, we will add the powers. more formulas to remember :– [tex] {x}^{m} \div {x}^{n} = {x}^{m – n} \\ ( {x}^{m} )^{n} = {x}^{m \times n} [/tex] hope it helps. Reply

Answer:[tex] {( \frac{2}{5}) }^{ – 4} \\ [/tex]

Step-by-step explanation:[tex]( \frac{2}{5} ) ^{ – 2} \times {( \frac{2}{5} )}^{ – 2} \\ = {( \frac{2}{5} )}^{ – 2 + ( – 2)} \\ = {( \frac{2}{5} )}^{ – 2 – 2} \\ = {( \frac{2}{5} )}^{ – 4} [/tex]

itdonebytheformula:–[tex] {x}^{m} \times {x}^{n} = {x}^{m + n} [/tex]Wherebasesaresameandwehavetomultiplythem,wewilladdthepowers.moreformulastoremember:–[tex] {x}^{m} \div {x}^{n} = {x}^{m – n} \\ ( {x}^{m} )^{n} = {x}^{m \times n} [/tex]hopeithelps.